Haunted landscapes : super-nature and the environment - Heholt, Ruth; Downing, Niamh (Place, memory, affect., 2016)
Examines the concept of landscape as a multitude of places and spaces haunted by spectres, memory, trauma and nostalgia in literature, art and film from Victorian times to the present.